Angiogenic inhibition therapy, a sliding mode control adventure. (July 2020) - Doruk, Reşat Özgür
Highlights: A closed loop inhibitory agent rate administration law is derived. The approach utilizes the second order dynamical model of angiogenic inhibition. Sliding mode control theory is applied in the derivation of the closed loop inhibitory agent injection laws. The results can be adapted for targeted molecular therapy which is applied as a modern cancer treatment approach. Abstract: Background and Objective: A sliding mode based inhibitory agent injection law is derived using angiogenic inhibition model of cancer progression which describes the variation of tumor and supporting vasculature volumes in targeted molecular therapies. Methods: The closed loop injection laws are derived by applying sliding mode control method which is known as a robust control approach. It is beneficial especially when there are parametric uncertainties in the dynamical model of the plant. In this research plant is represented by angiogenic cancer progression model. Random uncertainties are introduced to the physiological rate constants and simulations are repeated several times to see the deviations in the states and inhibitory agent rates. Results: Smooth inhibitory agent injection laws are obtained from the developed approach. Several different control configurations reveal that, it is possible to decrease the setup time to 6.1 days. A few of those settings failed to generate a satisfactory result. It appeared also that the sliding surface parameters have a distinct effect on the closed loop performance. Appropriate choice of the sliding surface parameters allows one to have a robust closed loop treatment where the deviation from the nominal response is relatively lower. Discussion: The lowest setup time obtained in this research is 6.1 days. This appear shorter than other similar studies where the plant is represented by the same or similar models. In the cases where the setup time is relatively shorter, the inhibitory agent injection requirement is higher than the other cases. This result seems larger compared to similar studies however the inhibitory agent stays at high levels for a short duration. In addition, the existence of uncertainty may also lead to an increase in the inhibitory agent rate requirements. Nevertheless, the results of the study reveals that one can reduce the tumor volume in a finite time without the necessity of constant application of high dosage inhibitory agent.